Parental sex-dependent effects of either maternal or paternal eNOS deficiency on the offspring’s phenotype without transmission of the parental eNOS deficiency to the offspring - Zhang, Xiaoli; Reichetzeder, Christoph; Liu, Yvonne; Hocher, Johann-Georg; Hasan, Ahmed A.; Lin, Ge; Kleuser, Burkhard; Hu, Liang; Hocher, Berthold (Frontiers in Physiology, 2023)
Preclinical animal studies and clinical studies indicate that both maternal as well as paternal genetic alterations/gene defects might affect the phenotype of the next generation without transmissions of the affected gene. Currently, the question of whether the same genetic defect present in the mother or father leads to a similar phenotype in the offspring remains insufficiently elucidated. In this head-to-head study, we crossbred female and male mice with heterozygous endothelial eNOS knockout (+/-eNOS) with male and female wild-type (wt) mice, respectively. Subsequently, we compared the phenotype of the resulting wt offspring with that of wt offspring born to parents with no eNOS deficiency. Wt female offspring of mothers with heterozygous eNOS showed elevated liver fat accumulation, while wt male offspring of fathers with heterozygous eNOS exhibited increased fasting insulin, heightened insulin levels after a glucose load, and elevated liver glycogen content. By quantitative mass-spectrometry it was shown that concentrations of six serum metabolites (lysoPhosphatidylcholine acyl C20:3, phosphatidylcholine diacyl C36:2, phosphatidylcholine diacyl C38:1, phosphatidylcholine acyl-alkyl C34:1, phosphatidylcholine acyl-alkyl C36:3, and phosphatidylcholine acyl-alkyl C42:5 (PC ae C42:5) as well as four liver carbon metabolites (fructose 6-phosphate, fructose 1,6-bisphosphate, glucose 6-phosphate and fumarate) were different between wt offspring with +/-eNOS mothers and wt offspring with +/-eNOS fathers. Importantly, fumarate was inversely correlated with the liver fat accumulation in female offspring with +/-eNOS mothers and increased liver glycogen in offspring of both sexes with +/-eNOS fathers. The qRT-PCR results revealed that the gene expression patterns were different between wt offspring with +/-eNOS mothers and those offspring with +/-eNOS fathers.Different gene expression patterns were correlated with different observed phenotypic changes in male/female offspring born to mothers or fathers with a heterozygous eNOS genotype. In conclusion, the identical parental genetic alteration (heterozygous eNOS deficiency), without being passed on to the offspring, results in distinct metabolic, liver phenotype, and gene expression pattern variations depending on whether the genetic alteration originated from the father or the mother.